Survey on the elastoplastic behavior in the process of rotary draw bend of tubes - Hurtado, Jorge Luis; Santana Milán, Raúl; Padrón Soroa, Sergio (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Rotary draw bend of tubes is a process widely used in various industrial applications, such as automotive, aerospace and others. Plastic-deformation theory is employed to investigate the plastic deformation in pipe and tube bending. The major contribution of this paper is that it provides solutions to seven common tube-bending questions, these are: (1) deviation of neutral axis; (2) bending moment; (3) calculation of the feed preparation length of the bend; (4) determining of the angle and radii of springback compensation (5) wall thickness change; (6) flattening and (7) wrinkling on the inside of the curve. This paper shows a procedure to evaluate the influence of axial effort and internal pressure in the thickening or thinning of the wall and the variation of the radius in the cross section of the tube. A new mathematical model and its evaluation using software are discussed.